O desafio da psicologia ante o envelhecimento: análise da grade curricular dos cursos de graduação em psicologia nas regiões Sudeste e Sul - Santos, Ednéia Salviano da Silva (2013)
The objective of this research was to analyze how psychology courses are working with the theme of ageing and old age, and to confirm whether, with the growing senior citizen population, universities are preparing qualified professionals to work in this field, increasing the area of study beyond the physical aspects of this population to include the psychosocial approach. To do this, a thorough analysis of the curriculums of public and private universities of Brazil s south and southeast regions, which comprise the country s largest number of over 60 s, was undertaken. Based on bibliographic research on the theme of the ageing process and old age, it was found that the Human Development Theory should be applied beyond adulthood to include senior citizens over 80, and should also consider the familial, social and psychological aspects of this age group. Furthermore, documentary studies were undertaken in order to use, compare and analyze data in the public domain, specifically obtained on the internet, about syllabuses and curriculums posted on academic institutions websites. Eleven (11) universities that offer psychology courses in their curriculum with mandatory or elective classes either on or about ageing or old age were analyzed. The social role of universities includes the need for a greater awareness of their own importance in the formation of professionals that can meet society s current needs, as stated in the national curriculum guidelines. However, it was found that current thinking from the biopsychosocial perspective on human ageing is barely addressed by the undergraduate psychology programs studied. Psychology professionals, as members of the health care profession, should be well versed, upon graduating, in the theories of the ageing process and old age, in addition to those of adult development, and be sure of their own views on ageing, illness, and death. In response to these shortcomings, and the changing demographics of the country, the creation of national curriculum guidelines for education on ageing and human longevity for psychology courses is suggested